Characterization of SixOyNz coating on CF/PPS composites for space applications - de O.C. Cintra, Maria Paula [UNESP]; Santos, Alberto L. [UNESP]; Silva, Patrícia; Ueda, Mario; Janke, Andreas; Jehnichen, Dieter; Simon, Frank; Botelho, Edson C. [UNESP] (Elsevier, 2018)
This work deals with the processing and surface treatment of thermoplastic composites carbon fibers/Polyphenylene sulfide (CF/PPS) for aerospace applications. After the production of the thermoplastic composites through hot compression molding, a silicon deposition was carried out on its surface using Plasma Enhanced Chemical Vapor Deposition (PECVD). Then, the Plasma Immersion Ion Implantation (PIII) process was executed on the silicon coated samples to create an amorphous silicon nitride layer. Subsequently, the coated and uncoated samples were characterized by means of the following techniques: optical microscopy, atomic force microscopy (AFM), X-ray diffraction (XRD) and X-ray excited photoelectron spectroscopy (XPS). By analyzing all the results obtained from the characterizations, it was concluded that a layer of amorphous silicon oxynitride was generated on the CF/PPS composite without damaging it. This result is an innovative step concerning the application of this material in a space environment (low earth orbit).
Keywords: Advanced composites; Plasma enhanced chemical vapor deposition; Plasma immersion ion implantation; Silicon oxynitride; Spatial environment